Technical change and the rate of profit in Classical-Marxian models of economic growth - Deepankar Basu (University of Massachusetts, Department of Economics, 2024)
I study the effect of technical change on the equilibrium profit rate in Classical-Marxian models of economic growth with alternative closures. In each model, capitalists adopt a new technique of production only if it will increase the profit rate given their expectations about the movement of the real wage rate. The accumulation rate depends on a threshold rate of profit, below which capitalists do not invest. I consider three alternative closures: (a) a constant real wage rate (relevant for a labor surplus economy); (b) a constant wage share (relevant for an advanced capitalist economy with strong labor); and (c) a constant unemployment rate (relevant for an advanced capitalist economy with weak labor). For the model of the advanced capitalist economy with strong labor, the profit rate can fall after viable technical change irrespective of capitalists' expectations about the trajectory of the real wage rate after technical change. For models of the labor surplus economy and the advanced capitalist economy with weak labor, the equilibrium rate of profit can fall after viable technical change only if capitalists' choice of technique had been based on an expected fall in the real wage rate after technical change.
hdl:20.500.14394/54702
Keywords: B51; E11; O41; 330; economic growth; technical change; falling rate of profit